Slova v čase a prostoru: Z Textů rakví z lufaovy hrobky v Abúsíru // Words in time and space: The Coffin Texts in the tomb of lufaa at Abusir - Diana Míčková (Pražské Egyptologické Studie, 2016)
The present study dea ls with textual tradition and transmission in the Late Period, focusing on selected spells from the Coffin Texts from the shaft tomb of the priest Iufaa at A bu sir. Changes in the orthography, palaeography, grammar and content of the texts between the Middle Kingdom (or sometimes even the Old Kingdom) and the Late Period indicate that the priests and scribes ofthe Late Period, who read and copied these texts, understood them and were able to modify the parts that were unintelligible to them or no longer in keeping with their world view and change them e.g. to comply with contemporary religious concepts. This does not, however, mean that the Late Period copyists were immune to misinterpretation and error. Since many spell s found in Iufaa 's tomb are not preserved elsewhere in the Late Period and sometimes exist in highly fragmentary versions from the Middle Kingdom, analyses oflufaa 's versions of these texts significantly contribute to the existing translations and interpretations of some Coffin Texts spells.